2016
DOI: 10.1016/j.neo.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Upstream and Downstream Co-inhibition of Mitogen-Activated Protein Kinase and PI3K/Akt/mTOR Pathways in Pancreatic Ductal Adenocarcinoma

Abstract: BACKGROUND: Extensive cross talk exists between PI3K/Akt/mTOR and mitogen-activated protein kinase (MAPK) pathways, and both are upregulated in pancreatic ductal adenocarcinoma (PDAC). Our previous study suggested that epidermal growth factor receptor inhibitor erlotinib which acts upstream of these pathways acts synergistically with PI3K inhibitors in PDAC. Horizontal combined blockade upstream and downstream of these two pathways is therefore explored. METHODS: Erlotinib paired with PI3K inhibitor (BYL719) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
(53 reference statements)
3
30
0
Order By: Relevance
“…Results show that there was a lack of apoptosis induction which corresponds also with the observation from other groups [37], [44]. Although apoptosis can be induced independently of caspase activation, resistance to TKIs like erlotinib may be caused by blocking apoptosis induction [45], [46]. Thus, successful induction of cancer cell death can be accomplished by combination therapies, for example, with HDAC inhibitors [37].…”
Section: Discussionsupporting
confidence: 77%
“…Results show that there was a lack of apoptosis induction which corresponds also with the observation from other groups [37], [44]. Although apoptosis can be induced independently of caspase activation, resistance to TKIs like erlotinib may be caused by blocking apoptosis induction [45], [46]. Thus, successful induction of cancer cell death can be accomplished by combination therapies, for example, with HDAC inhibitors [37].…”
Section: Discussionsupporting
confidence: 77%
“…Limited published preclinical research focusing on this issue in PDAC reported similar cytotoxic activity of perifosine in PANC-1, MIA PaCa-2, and AsPC-1 cells [55]. Sensitivity to perifosine in the PDAC cells also fell within the range of IC 50 values previously reported in PDAC cell lines and spheroids for other Akt inhibitors, such as NVP-BEZ-235 [56, 57]. …”
Section: Discussionsupporting
confidence: 61%
“…It is already known that in PDAC cells, dual PI3K-mTOR inhibition induces rapid overactivation of MAPK pathway through a PI3K-independent pathway [67], and that drug resistance may be overcome by inhibition of parallel oncogenic-dependent pathways, such as with the dual MEK and PI3K/mTOR blockade [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutations in Akt in addition to KRAS mutations may accelerate PDAC development [33]. Recently, targeting the PI3K/Akt pathway in combination with blockade of MAPK has been shown to increase cell cycle arrest and apoptosis in pancreatic cancer cell lines [34]. We previously reported that AR-42 induces dephosphorylation of Akt through release of PP1 from PP1-HDAC complexes independent of histone acetylation [19].…”
Section: Discussionmentioning
confidence: 99%